On the Monophyly and Relationships of Several Genera of Hylini (Anura: Hylidae: Hylinae), with Comments on Recent Taxonomic Changes in Hylids - Faivovich, Julian; Pereyra, Martin O.; Celeste Luna, Maria; Hertz, Andreas; Blotto, Boris L.; Vasquez-Almazan, Carlos R.; McCranie, James R.; Sanchez, David A.; Baeta, Delio [UNESP]; Araujo-Vieira, Katyuscia; Koehler, Gunther; Kubicki, Brian; et al. (Soc Brasileira Herpetologia, 2018)
We present a molecular phylogenetic analysis of the hylid tribe Hylini, with the goals of testing the monophyly of the genera Duellmanohyla, Isthmohyla, and Ptychohyla and providing a discussion on the monophyly of Bromeliohyla, Charadrahyla, Ecnomiohyla, Exerodonta, Megastomatohyla, and Sarcohyla. Our results indicate the paraphyly of Ptychohyla, with Bromeliohyla and Duellmanohyla nested within it, and, as in previous analyses, the paraphyly of Duellmanohyla (due to Ptychohyla legleri and P. salvadorensis being nested within it). To resolve this situation, we restrict the contents of Ptychohyla, redelimit those of Duellmanohyla and Bromeliohyla, and erect two new genera, one to include the former Ptychohyla panchoi and P. spinipollex, and the other for the former Ptychohyla acrochorda, P. sanctaecrucis, P. zoque, and tentatively, P. erythromma. Exerodonta as currently defined is not monophyletic, inasmuch as Exerodonta juanitae is nested within Charadrahyla. Consequently, we transfer this species and, tentatively, E. pinorum to Charadrahyla. Also, we discuss some possible taxonomic problems within Exerodonta. Our results indicate that Isthmohyla is polyphyletic, the bromeliad-dwelling Isthmohyla melacaena being the sister taxon of our only exemplar of Bromeliohyla, B. bromeliacia. For this reason, we transfer I. melacaena to Bromeliohyla, rendering Isthmohyla monophyletic. The former Isthmohyla pictipes Group is shown to be paraphyletic due to having the non-monophyletic I. pseudopuma Group within it. Accordingly, we recognize a redelimited I. pseudopuma Group (contents:I. infucata and I. pseudopurna), an I. zeteki Group (contents: I. pica doi and I. zeteki), and a newly defined I. tica Group (contents: I. angustilineata, I. calypsa, I. debilis, I. graceae, I. lancasteri, I. pictipes, I. tica, I. rivularis, and, tentatively, I. insolita and I. xanthosticta). The three groups of Isthmohyla are supported by molecular evidence with jackknife support values > 90%, and two of them by putative morphological synapomorphies. We discuss the recognition of Dryophytes, Hyliola, Rheohyla, and Sarcohyla and whether it is useful to recognize Anotheca, Diaglena, and Triprion as three distinct, monotypic genera. Finally, we discuss a recent taxonomic proposal involving changes in rank and from ranked to unranked names in hylids that overall we consider to have been poorly justified and only superficially discussed.
Keywords: Amphibia; Phylogeny; Systematics